A universal model of three-phase asynchronous motors for electrical power system analysis - Laura Collazo Solar; Ángel A. Costa Montiel; Miriam Vilaragut Llanes; Vladimir Sousa Santos; Carlos de la Incera Núñez (Institute of Advanced Engineering and Science, 2023)
The high incidence of three-phase asynchronous motors (TAM) in global energy consumption and its influence on the operation of electrical systems makes it necessary to develop models that allow their analysis effectively. Based on this, this paper presents a universal model of TAM based on the relationship between the active and reactive power of the TAM and the deviation of voltage and frequency. It can be applied to any general-purpose TAM and is very useful when representing these motors in electrical power system studies. The model parameters were obtained from a statistical analysis performed on 70 TAM of different classifications. The results are validated by comparing them with those obtained from the solution of the equivalent circuit, demonstrating its validity by less than 6% errors.